Teacher professional development program to improving pedagogical content knowledge: a review of empirical research - Y F Kasi; A Widodo; A Samsudin; R Riandi (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2021)
This study analyzed articles of the journals in Scopus database to review empirical research about the teacher professional development (TPD) program to improving science teacher pedagogical content knowledge (PCK) in the year 2008-2020. This study also explains the use opportunity of the professional development program in Indonesia. Three stages were used to analyze the article: 1) identify the articles, 2) classification based on model TPD, and 3) code and analyze all reviewed articles. Based on the above stages, 41 articles were selected for further analyze in the model of TPD program focus to improve PCK on teachers. Six models were collected are lesson study, mentoring, workshop, using CoRe and PaP-eRs, based on technology, and based on role-playing, ethnoscience. The result showed six models in an analysis of the article had a positive effect on improving the PCK on teachers and prospective teachers. However, one research explains that model workshops, not enough to improving PCK on science teachers. A case in Indonesia the combination of model TPD from this review analysis is believed to improve the PCK of science teachers. For future studies are needed to harness the resource combination of the model TPD to improving teachers’ knowledge and skills